Community Based Tourism- The Attraction Of ‘Embhan’ Community In Kampung Semban, Sarawak. - Yakup, Mohd Rafee; Sylvester Wielding, Jussem; Awangko Hamdan, Awang Arshad; Hakimi, Halim; Hishamudin, Siri; Mohd Zamhari, Abol Hassan (Universiti Malaysia Sarawak, 2012)
Kampung Semban is a remote village and currently renowned for its Embhan community which is one of the sub-ethnic groups of Bidayuh in Sarawak. This community has been widely portrayed in the local tourism industry through the spectacular appearance of their last remaining ‘Ring Ladies’. These special ladies wore brass-rings around their calves called ‘rasung’, and brass-rings around the forearms known as ‘ruyang’. However, based on research, the researcher found out that there are more than just the ‘Ring Ladies’ factor that draws visitors to Kampung Semban. This paper aims to describe the findings based on the researcher’s experience and observation relating to the additional attraction factors in Kampung Semban and propose it in promoting and boosting this industry further. The researcher anticipated that the potential of these findings could be employed as a proposal in enhancing the development of this competitive community-based tourism in BIMP-EAGA region particularly in Malaysia. To conclude, it is hope that this writings could also be utilized as part of the contribution towards enriching the visual references and records pertaining to the existing community-based tourism in Kampung Semban.